Analysis of Investment Decision Assessment Using the Net Present Value (NVP) Method at PT Bank Mandiri (Persero) Tbk - Muqtashida, Amalia Aura; Benedicta, Hellena; Suhaimi, Nurnisaa Binti Abdullah (International Journal of Mathematics, Statistics, and Computing, 2024)
This paper explores the fundamental elements of a robust business management strategy, essential for sustained success in the dynamic business landscape. It delves into crucial components such as investment decision-making, comprehensive planning, business development, and judicious risk-taking. These strategic decisions not only influence immediate financial performance but also contribute to long-term benefits such as market growth and heightened competitiveness. Focusing on the banking sector, the paper acknowledges the potential for substantial returns juxtaposed with inherent risks. Emphasizing that these risks are manageable, particularly in the stock market, it advocates for a meticulous approach to investment decision analysis. The strategic choices made in this process play a pivotal role in maximizing returns while minimizing the impact of stock market risks. With a preference for the Net Present Value (NPV) method highlighted in the literature review, the paper underlines the significance of comprehensive investment decision analysis.